Danlian-Tongmai formula improves diabetic vascular calcification by regulating CCN3/NOTCH signal axis to inhibit inflammatory reaction - Wenting Wang; Yiwen Li; Mengmeng Zhu; Qian Xu; Jing Cui; Yanfei Liu; Yanfei Liu; Yue Liu (Frontiers in Pharmacology)
BackgroundVascular calcification (VC) commonly occurs in diabetes and is associated with cardiovascular disease incidence and mortality. Currently, there is no drug treatment for VC. The Danlian-Tongmai formula (DLTM) is a traditional Chinese medicine (TCM) prescription used for diabetic VC (DVC), but its mechanisms of action remain unclear. This study aims to elucidate the effects of DLTM on DVC and explore the underlying mechanisms of action.MethodsUltra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS) was used to identify the metabolites of DLTM. A DVC rat model was established using streptozotocin (STZ) combined with vitamin D3 (VitD3). The effects of DLTM on DVC were evaluated through alizarin red staining, calcium deposition, and changes in osteogenic and contractile markers. The specific molecular mechanism of DLTM in treating diabetic VC was comprehensively analyzed by transcriptomics, molecular docking and in vivo experimental verification.ResultsWe identified 108 major metabolites of DLTM. In vivo, high-dose DLTM significantly alleviated VC in diabetic rats. Transcriptomic analysis showed that DLTM treatment markedly altered the transcriptomic profile of rat aortas, which was associated with regulating the CCN3/NOTCH signaling pathway, promoting vascular smooth muscle contraction, and inhibiting the inflammatory responses. Molecular docking and molecular dynamics simulation demonstrated strong binding interactions between DLTM metabolites and key molecules within the CCN3/NOTCH pathway, including NOTCH1, DLL1, DLL4, hes1, and hey1. In vivo experiments confirmed that DLTM could upregulate CCN3, inhibit the activation of NOTCH signaling ligands DLL1 and downstream transcription factors hes1 and hey1, and reduce the release of inflammatory cytokines IL6, IL1β, and TNFα.ConclusionDLTM alleviates DVC by regulating the CCN3/NOTCH signaling axis to inhibit inflammatory responses. Our research provides experimental basis for clinical treatment and drug transformation of diabetic VC.